Integrated Tensile Fabric Curved-Ceiling with Lightshelf for Daylight Performance in Office - Limsatjapanit, Tippawan; Wankanapon, Pimonmart (Journal of Architectural/Planning Research and Studies (JARS), 2015)
This research presented the optimization of lightshelf performance with curved ceiling geometries. Aninnovative design of Polyester - PVC Fabric curved ceiling using tensile structure for the purpose of applyingto existing rooms are designed, developed and tested using simulation models in DIALux. The Illuminancelevel, the reach of daylight admission, the distribution uniformity and the visual quality using luminance ratiowere assessed on a working plane of commonly found open-plan office spaces with the depth of 8 meters ormore. The Polyester PVC fabric optical properties are as followed; visible reflectance (e) 0.88, and visibletransmittance 0.07 (t). The study compared the results of a room installed with lightshelf (internal 0.5 m., andexternal 1.00 m.) and the regular ceiling to the room with tensile fabric curved ceiling of 4 types, 1) concavecurve facing openings 2) concave curve facing away from openings 3) convex curve facing openings and 4)convex curve facing away from openings. The radius of the curvature and the installation dimension affectingthe daylight performance are also studied. The application of the ceiling's tensile structure with the benefit ofits lightweight is presented. The simulation results shown that the ceiling form of concave curve facing intothe room are the best geometries to increase the reach of daylight deeper into the space for 1 meter morewith more uniformity.